2022
DOI: 10.3389/fmed.2022.853759
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Multidimensional Population-Based Healthy Aging Scale: Results From the China Health and Retirement Longitudinal Study

Abstract: BackgroundThe World Health Organization proposed a multidimensional concept of healthy aging in 2015; there was limited evidence about how the concept was constructed and measured. The current study aims to develop a health aging scale (HAS) following the WHO framework and validate it using data from the China Health and Retirement Longitudinal Study (CHARLS).MethodsA total of 13,233 adults aged ≥ 45 years old from the CHARLS included in current study. Based on the WHO framework, 37 self-reported indicators we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Such domains as vitality, cognition, and psychology are the most commonly used, i.e., 76% of the reviewed studies reported them. Such domains as locomotion and sensory were reported in only 4–5 studies ( 7 , 10 , 23 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such domains as vitality, cognition, and psychology are the most commonly used, i.e., 76% of the reviewed studies reported them. Such domains as locomotion and sensory were reported in only 4–5 studies ( 7 , 10 , 23 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…We selected the established factors that have been clearly identified in previous research as control variables for healthy aging (Appendix 2 in the Supplement), including: physical condition (chronic diseases, teeth) [ 2 4 , 34 , 35 , 38 , 40 ], SES (education, ACE, household income) [ 3 , 4 , 6 , 8 , 9 , 34 , 35 , 40 44 ], lifestyle habits (smoke, drink) [ 3 , 6 , 7 , 34 , 35 , 41 , 43 , 45 ], and demographic factors (geographical distribution, urban–rural distribution, age, gender, and marital status) [ 3 , 4 , 6 , 9 , 34 , 35 , 40 , 42 ].…”
Section: Methodsmentioning
confidence: 99%